Major and Trace Airborne Elements and Ecological Risk Assessment: Georgia Moss Survey 2019–2023 - Omari Chaligava; Inga Zinicovscaia; Alexandra Peshkova; Nikita Yushin; Marina Frontasyeva; Konstantin Vergel; Makhabbat Nurkassimova; Liliana Cepoi (Plants)
The study, carried out as part of the International Cooperative Program on Effects of Air Pollution on Natural Vegetation and Crops, involved collecting 95 moss samples across the territory of Georgia during the period from 2019 to 2023. Primarily samples of Hypnum cupressiforme were selected, with supplementary samples of Abietinella abietina, Pleurozium schreberi, and Hylocomium splendens in cases of the former’s absence. The content of 14 elements (Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, S, Sr, V, and Zn) was detected using Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), while the Hg content was determined using a Direct Mercury Analyzer. To identify any relationships between chemical elements and to depict their sources, multivariate statistics was applied. Principal component analysis identified three main components: PC1 (geogenic, 43.4%), PC2 (anthropogenic, 13.3%), and PC3 (local anomalies, 8.5%). The results were compared with the first moss survey conducted in Georgia in the period from 2014 to 2017, offering insights into temporal trends of air quality. Utilizing GIS, a spatial map illustrating pollution levels across Georgia, based on the Pollution Load Index, was generated. The Potential Environmental Risk Index emphasized significant risks associated with mercury and cadmium at several locations. The study highlights the utility of moss biomonitoring in assessing air pollution and identifying hotspots of contamination. The findings from this study could be beneficial for future biomonitoring research in areas with varying physical and geographical conditions.